Variability of the Ability of Complex Microbial Communities to Exclude Microbes Carrying Antibiotic Resistance Genes in Rabbits - Achard, Caroline Stéphanie; Dupouy, Véronique; Siviglia, Suzanne; Arpaillange, Nathalie; Cauquil, Laurent; Bousquet-Mélou, Alain; Zemb, Olivier (Frontiers in Microbiology, 2019)
Reducing antibiotic use is a necessary step towards less antibiotic resistance in livestock, but many antibiotic resistance genes can persist for years even in an antibiotic-free environment. Here we investigated the potential of 3 fecal complex microbial communities from antibiotic-naive does to drive the microbiota of kits from antibiotic-exposed dams and outcompete bacteria carrying antibiotic resistant genes. The fecal complex microbial communities were either orally delivered or simply added as fresh fecal pellets in 4 to 5 nests who were kept clean from maternal feces. Additionally, 4 nests were cleaned for the maternal feces and 5 nests were handled according to the common farm practice (i.e. cleaning once a week) as controls. At weaning, we measured the relative abundance of 26 antibiotic resistance genes, the proportion of Enterobacteriaceae resistant to tetracycline and sulphonamide antibiotics and the taxonomic composition of the microbiota by sequencing the 16S rRNA gene of one kit per nest. Changing the surrounding microbes of the kits can hinder the transmission of antibiotic resistance genes from one generation to the next but the 3 communities differed widely in their ability to orient gut microbes and in their impact on antibiotic resistance genes: The most efficient delivery of microbial community reduced the proportion of resistant Enterobacteria from 93% to 9%, decreased the relative abundance of 8 antibiotic resistance genes and changed the gut microbes of the kits at weaning. The less efficient did not reduce any ARG or modify the bacterial community. In addition, adding fecal pellets was more efficient than the oral inoculation of the anaerobic suspension derived from these fecal pellets. However we were unable to predict the outcome of the exclusion from the data of the donor does (species composition and abundance of antibiotic resistance genes). In conclusion we evidenced major differences between microbial communities regarding their ability to exclude the antibiotic resistance gene, but more work is needed to understand the components leading to a successful exclusion of antibiotic resistance genes from the gut. As a consequence, studies about the impact of competitive exclusion should use several microbial communities in order to draw general conclusions.